Botswana: Tracking wildlife in the Kalahari with a PDA - Liebenberg, Louis (Technical Centre for Agricultural and Rural Cooperation, 2005)
Louis Liebenberg discusses how CyberTracker software is helping a community in Botswana to monitor and manage local wildlife resources.